Тайна дочери пророка. Сердце Фатимы: [роман] / Ф. Вульф - Вульф Франциска (Мир книги, 2006)
Экземпляры: ф.6 (20171219) / Инвентарный номер: 2193 / Цена: / Сис.шифр: 84(4Гем)-4 / Авт.знак: В 88 / ГРНТИ: 17.82.31 / ББК: 84(4Гем)-445